Quantifying workspace and forces of surgical dissection during robot‐assisted neurosurgery. Issue 3 (29th June 2015) - Maddahi, Yaser; Gan, Liu Shi; Zareinia, Kourosh; Lama, Sanju; Sepehri, Nariman; Sutherland, Garnette R.
Abstract: Background: A prerequisite for successful robot‐assisted neurosurgery is to use a hand‐controller matched with characteristics of real robotic microsurgery. This study reports quantified data pertaining to the required workspace and exerted forces of surgical tools during robot‐assisted microsurgery. Methods: A surgeon conducted four operations in which the neuroArm surgical system, an image‐guided computer‐assisted manipulator specifically designed to perform robot‐assisted neurosurgery, was employed to surgically remove brain tumors. The position, orientation, and exerted force of surgical tools were measured during operations. Results: Workspace of the neuroArm manipulators, for the cases studied, was 60×60×60 mm 3 while it offered orientation ranges of 103°, 62° and 112°. The surgical tools exerted a maximum force of 1.86 N with frequency band of less than 20 Hz. Conclusions: This data provides important information specific to neurosurgery that can be used to select among commercially available, or further design a customized, haptic hand‐controller for robot‐assisted neurosurgical systems. Copyright © 2015 John Wiley & Sons, Ltd.